Bimbingan Konseling Islam bagi Anak Berkebutuhan Khusus: Model Konseling Inklusi (Jurnal Bimbingan dan Konseling Islam, 2018)
Every child is born of God's will, by His permission, accompanied by the wishes and wishes of the parents. But in reality, the child is born with the following advantages and disadvantages, including children born with the condition of children in general or normal, but also there are born with abnormalities, physically and psychologically, which is then called the child with special needs. Children with special needs are students (under 18 years old) who have difficulty in following the learning process because of physical, emotional, mental, social, and or have special intelligence and talents. Special needs children need stress-free life, caring for friends and family, positive models, opportunities for success at school and other activities in the community. Therefore, for special needs children need the pattern of education and counseling Islamic inclusion, which has a broader range, so that counselors will conduct guidance and counseling covering the dimensions of (1) Educational Dimensions, (2) Developmental Dimensions, (3) Preventive Dimensions, (4) Ecological Dimensions, (5) Futuristic Dimensions. This is where the role of the counselor becomes so important in conducting the counseling and mentoring process for teachers, parents and children with special needs themselves, to assist in the implementation of the planned individual programs.